2017
DOI: 10.1001/jamapsychiatry.2017.1472
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Medication Use and Performance on Higher Education Entrance Tests in Individuals With Attention-Deficit/Hyperactivity Disorder

Abstract: Association between medication use and performance on higher education entrance tests in individuals with Abstract IMPORTANCEIndividuals with attention-deficit/hyperactivity disorder (ADHD) are at greater risk for academic problems. Pharmacologic treatment is effective in reducing core symptoms of ADHD, but it is unclear whether it helps to improve academic outcomes. OBJECTIVETo investigate the association of the use of ADHD medication and the performance of higher education entrance test in individuals with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 53 publications
(109 reference statements)
3
20
0
Order By: Relevance
“…The children also received other supportive and educational treatments. Similar improvement in learning abilities by pharmacological treatment was demonstrated in adults by Lu et al [39] as well as by other investigators. Improved educational achievements also have benefits in reducing crime rate and in decreasing accidents and drug dependence.…”
Section: Introductionsupporting
confidence: 87%
“…The children also received other supportive and educational treatments. Similar improvement in learning abilities by pharmacological treatment was demonstrated in adults by Lu et al [39] as well as by other investigators. Improved educational achievements also have benefits in reducing crime rate and in decreasing accidents and drug dependence.…”
Section: Introductionsupporting
confidence: 87%
“…This is line with previous studies which demonstrated clinical benefits of psychostimulant medication at 12 months [ 42 ] and 24 months [ 3 , 4 ]; however, the clinical benefits of psychostimulant medication (when naturalistically assessed) are not empirically supported for longer follow-up periods of 2–8 years [ 43 45 ]. Despite this, recent epidemiological studies have found that continued controlled medication intake can have positive benefits for patients with ADHD [ 46 48 ]. However, Swanson et al [ 49 ] reported that at 12–16-year follow-up of long-term medication use (both consistent and inconsistent use over this time period) was not associated with reduced symptom severity, but it was associated with decreased adult height.…”
Section: Discussionmentioning
confidence: 99%
“…7,14,15 Observational studies exploring short-term effects have found converging evidence. 16,17 One recent study using Swedish register data found that, although of small effect, individuals (mean age 22.2 years) performed better on higher education entrance tests during medicated than unmedicated periods 16 and another study in children using a similar design found that GPA was higher during stimulant adherent periods. 17 Ideally, the long-term association between ADHD medication and school performance should be examined in large prospective RCTs, but since such trials are problematic (e.g., patients assigned to a long-term untreated control arm may seek out medications elsewhere) and unethical (e.g., withholding treatment with known benefits), future research in this area must rely on findings from observational designs.…”
Section: Introductionmentioning
confidence: 99%